Risk factors for Clostridium difficile infection in C. difficile colonized ICU patients. (4th October 2017) - Zhou, Yuan; Lewis, Larissa; McIntosh, Michelle; Fang, Ferric C; Pergamit, Ronald; Dellit, Timothy; Lynch, John B
Abstract: Background: Clostridium difficile is a major cause of healthcare-associated infections leading to significant morbidity and mortality; however, data-driven interventions to decrease C. difficile infections (CDI) are lacking due to an incomplete understanding of disease transmission and risk factors. Asymptomatic C. difficile carriers may be an important source of nosocomial transmission and disease but few studies have examined colonized patients who later develop CDI. We describe risk factors for the development of CDI in a critical care population screened for C. difficile colonization. Methods: All patients admitted to our medical or trauma ICUs were screened for toxigenic C. difficile by PCR via rectal swab. Colonized patients were placed in contact enteric precautions for their entire hospitalization and monitored for signs and symptoms of CDI. Retrospective chart review assessed risk factors associated with development of CDI. Results: 868 rectal swabs were collected from 4/01/16 to 10/31/16. 40 patients were colonized with C. difficile on ICU admission and 20 developed symptomatic CDI (Table 1). Risk factors for CDI in colonized patients include enteral feeding and exposure to antibiotics (Table 2). Conclusion: 50% of C. difficile colonized ICU patients progressed to symptomatic CDI during their hospitalization. Antibiotic use was a significant risk factor for CDI. C. difficile carriers may be a particularly vulnerable population for CDI, warranting further investigation for early identification of colonized patients and strategies for infection prevention. Disclosures: F. C. Fang, BioFire: Collaborator, Consultant and Scientific Advisor, Consulting fee, Research support and Speaker honorarium; Cepheid: Collaborator, Consultant and Scientific Advisor, Consulting fee, Educational grant, Research support and Speaker honorarium